Controlling embedded carbon emissions of sectors along the supply chains: A perspective of the power-of-pull approach. (15th November 2017) - Wang, Zhen; Wei, Liyuan; Niu, Beibei; Liu, Yong; Bin, Guoshu
Highlights: Input-Output analysis was used to extract final use induced networks. Power-of-pull was applied to identify key sectors of networks. Power-of-pull is simpler than SPA, but provides equivalent results. Energy and raw material providers should be controlled. Abstract: The industrial sector is a major source of China's major CO2 emissions. In 2012, the emissions embedded in the final-use-induced intermediate CO2 flows contributed to approximately 91.2% of the total emissions. Hence, controlling CO2 emissions along supply chains could have a significant contribution in achieving the climate mitigation goal to which the Chinese government has been committed. In this study, we first extracted final-use-induced CO2 transfer networks from input-output tables, and then applied the power-of-pull approach to the networks to identify the key sectors significantly affecting the CO2 emissions of each targeted sector's supply chains. Our results showed that each sector itself has significant power of pulling their emissions. Energy and raw material providers have played an essential role in pulling other sectors' emissions in the past years. The results of all sectors can easily construct a network reflecting the system's characteristics. And the power-of-pull approach could easily be integrated with the structural path analysis. Our proposed approach has the potential in helping policy making by offering a new perspective.